Caffeine effects on spatial memory using morris water maze in BALB/C mice - Amirudin, Nur Farahim (2015)
Leaming and memory are part of cognitive functions that are essential in human. Caffeine is known to be a stimulant on the central nervous system. It is suggested to have effect on learning and memory through its antagonism action on adenosine receptor. This study was performed to observe the effects of caffeine on spatial memory in BALB/c mice using Morris Water Maze. The results showed that caffeine does not have effects on the time spent in the original platform quadrant of the pool as compared to the saline. Interestingly, caffeine-treated mice with dose 3 mg/kg spent more time in the quadrant than dose 1 mg/kg. On the other hand, caffeine did reduce the distance to get to the quadrant that containing the original platform. Although, the value was not significant, mice administered with caffeine 3 mg/kg has the lowest distance followed by caffeine 1 mg/kg and saline. Another procedure observed in this study was the latency for mice to reach the submerged platform during the acquisition training. Although mice from each group was not given drug treatment, only group 1 and 2 showed enhancement in term of their spatial memory as their latency is lower compared to the group 3. In summary, this present study documents the spatial memory-enhancing properties of caffeine administration in BALB/c mice. To further explain the cognitive effects of caffeine, the study should be repeated on different strain of mice with different doses of caffeine.